Paeoniflorin and Hydroxysafflor Yellow A in Xuebijing Injection Attenuate Sepsis-Induced Cardiac Dysfunction and Inhibit Proinflammatory Cytokine Production - Wang, Xin-Tong; Peng, Zhen; An, Ying-Ying; Shang, Ting; Xiao, Guangxu; He, Shuang; Chen, Xi; Zhang, Han; Wang, Yuefei; Wang, Tao; Zhang, Jun-Hua; Gao, Xiumei; et al. (Frontiers in Pharmacology, 2021)
Sepsis-induced myocardial dysfunction is a major contributor to the poor outcomes of septic shock. As an add-on with conventional sepsis management for over 15 years, the effect of Xuebijing injection (XBJ) on the sepsis-induced myocardial dysfunction was not well understood. The material basis of Xuebijing injection (XBJ) in managing infections and infection-related complications remains to be defined. A murine cecal ligation and puncture (CLP) model and cardiomyocytes in vitro culture were adopted to study the influence of XBJ on the infection-induced cardiac dysfunction. XBJ significantly improved the survival of septic-mice and rescued cardiac dysfunction in vivo. RNA-seq revealed XBJ attenuated the expression of proinflammatory cytokines and related signalings in the heart which was further confirmed on the mRNA and protein levels. Xuebijing also protected cardiomyocytes from LPS-induced mitochondrial calcium ion overload and reduced the LPS-induced ROS production in cardiomyocytes. The therapeutic effect of XBJ was mediated by the combination of paeoniflorin and hydroxysafflor yellow A (HSYA) (C0127-2). C0127-2 improved survival of septic mice, protected their cardiac function and cardiomyocytes while balancing gene expression in cytokine-storm related signalings, such as TNF-α and NF-κB. In summary, Paeoniflorin and HSYA are key active compounds in XBJ for managing sepsis, protecting cardiac function, and controlling inflammation in the cardiac tissue partially by limiting the production of IL-6, IL-1β, and CXCL2.